Microstructural evolution and micromechanical properties of thermally sprayed hydroxyapatite coating - Saber-Samandari, Saeed; Baradaran, Saeid; Nasiri-Tabrizi, Bahman; Alamara, Kadhim; Basirun, Wan Jefrey (Taylor & Francis, 2018)
The effects of preheating and annealing processes on the micromechanical features of thermally sprayed hydroxyapatite (HA) coatings were investigated. The results indicated that subsequent heat treatment at 700°C for 60 min promotes the development of a crystalline HA coating. The EDS line scan showed that the oxygen content was homogeneous along the thickness direction from the coating surface to the titanium–HA interface, whereas the calcium and phosphorus concentration gradually decreased at 7 μm from the interface. From the roughness profiles, the coatings on preheated substrates gave lower roughness compared to the coatings at room temperature. According to the nanoindentation results, the sample preheated at 300°C after annealing at 700°C exhibited an elastic modulus of 108.1 ± 6 GPa and hardness of 5.97 ± 0.3 GPa, which were almost 3% lower and 171% higher than the bare substrate, respectively.